Labour Standards in the Global Supply Chain; Village Fund and Labour Working Hours in Indonesia - Arifin, Bondi; Tenrini, Rita Helbra; Wicaksono, Eko; Rahman, Arif Budi; Wisnu Wardhana, Irwanda; Setiawan, Hadi; Damayanty, Sofia Arie; Solikin, Akhmad; Suhendra, Maman; Saputra, Acwin Hendra; Ariutama, I Gede Agus; Djunedi, Praptono; Handoko, Rudi (International Journal of Supply Chain Management, 2020)
Abstract- In the recent years, fashion brands and retailers in the West have introduced supplier’s codes of conduct to strengthen international labour standards in their supply chain. Village funds have been allocated since 2015, and increase overtime. In 2015, the allocation of village funds amounting to Rp.28.8 trillion increased to reach Rp60 trillion in 2018. Village funds were used to finance government administration, implementation of development, community development, and community empowerment. This research uses the difference-in-difference (DID) which is adapted to continuous treatment method to analyze the impact of village funds on the work of rural communities. The analysis uses "repeated" cross section data from SUSENAS 2012-2017. We found that an increase in village fund per capita was more likely to raise the labor hours in agriculture and service industries, primarily on non-Java islands. The recommendation of this study is the need for regulation to standardize the proportion of village funds allocation based on the demographic (or number of poor people) and geographical (land area) conditions of the regions. Moreover, increasing the effectiveness of organizational management can be implemented by increasing the capacity of village officials.